Espetáculo e produção de verdade na sociedade midiática: a Daspu na mídia impressa - Kersul, Maria Tereza (2009)
This master degree dissertation focuses on the publicizing of the fashion label Daspu, which has been developed by prostitutes from Rio de Janeiro, and the impacts of such publicizing on the receptors speech in regard to the spectacularized approach by the press media in reporting this label, as well as the their perceptions in regard to the prostitutes organized movement, whether as a resistance movement, or else as a compliance to power and to its social and moral values established in relation to prostitution. The methodology employed for the proposed survey comprises an exploratory documentary research for selecting a corpus, and a bibliographic research that supports the discussions about media culture spectacularization, as well as about power and resistance in contemporary society. As for the empiric research, we employed in-depth interview techniques to analyze the impacts of the media spectacularization on the prostitutes´N.G.O, who owns the label and a N.G.O. their leadership, and also a N.G.O. the reader/receptor audience of the chosen media vehicles. Considering that contemporary society is characterized by the hybridism between elements from both the spectacular and disciplinary societies, the media production surveyed here impacts individuals in odd ways, being a topic that, at the same time, entails reflection and a distant attitude. Our analysis about the publicizing of the Daspu label by the press media considers the spectacularization mechanisms that are present in the media texts examined, and the possibilities for both resistance and citizenship actions by the prostitutes group. It also ponders the receptors different readings of the media publicization, which involve issues ranging from the prostitutes victimization to their value assignment, the ways of the production of truth, as much as the power relations and knowledge relations set up in the contemporary world.